(h + 12) + (p + 24)
simplify the expression.
11 answers
h + 12 + p + 24 = h + p + 36
9/4x + 4 + 2x
First step is 9/4x + 2x = ?
First step is 9/4x + 2x = ?
The first step is to combine like terms:
9/4x + 2x = (9/4 + 8/4)x
Adding the numerators and keeping the common denominator:
(9 + 8)/4x = 17/4x
So, 9/4x + 2x simplifies to 17/4x.
The expression becomes:
17/4x + 4
9/4x + 2x = (9/4 + 8/4)x
Adding the numerators and keeping the common denominator:
(9 + 8)/4x = 17/4x
So, 9/4x + 2x simplifies to 17/4x.
The expression becomes:
17/4x + 4
No actually the answers are
15x + 12
5x + 4
x + 4
11/3x + 4
15x + 12
5x + 4
x + 4
11/3x + 4
Apologies for the confusion. Let's solve the expression correctly:
9/4x + 4 + 2x
To simplify, we first combine like terms:
9/4x + 2x = (9/4 + 8/4)x = (17/4)x
The simplified expression becomes:
(17/4)x + 4
There are no more like terms to combine, so this is the final simplified expression for 9/4x + 4 + 2x
9/4x + 4 + 2x
To simplify, we first combine like terms:
9/4x + 2x = (9/4 + 8/4)x = (17/4)x
The simplified expression becomes:
(17/4)x + 4
There are no more like terms to combine, so this is the final simplified expression for 9/4x + 4 + 2x
simplify this
5y - 2y + 1 + 4
5y - 2y + 1 + 4
To simplify the expression 5y - 2y + 1 + 4, we first combine like terms:
5y - 2y = (5 - 2)y = 3y
Next, we combine the constants 1 and 4:
1 + 4 = 5
Thus, the simplified expression is:
3y + 5
5y - 2y = (5 - 2)y = 3y
Next, we combine the constants 1 and 4:
1 + 4 = 5
Thus, the simplified expression is:
3y + 5
(5y - 1) + (-2y + 4)
To simplify the expression (5y - 1) + (-2y + 4), we first remove the parentheses:
5y - 1 + -2y + 4
Next, we combine like terms:
(5y - 2y) + (-1 + 4) = 3y + 3
Therefore, the simplified expression is:
3y + 3
5y - 1 + -2y + 4
Next, we combine like terms:
(5y - 2y) + (-1 + 4) = 3y + 3
Therefore, the simplified expression is:
3y + 3
(3/4x - 1) + (3/4x - 2)
first step is: (3/4x + 3/4x)
first step is: (3/4x + 3/4x)
The first step is to remove the parentheses and combine like terms:
(3/4x - 1) + (3/4x - 2)
To add the fractions with the same denominator, we add the numerators:
(3/4x + 3/4x) + (-1 - 2) = 6/4x + (-3)
Simplifying further:
6/4x - 3
Now, we can simplify the fraction by reducing it to lowest terms. Both the numerator and denominator can be divided by 2:
(6/2)(1/4x) - 3 = 3/2x - 3
Therefore, the simplified expression is:
3/2x - 3
(3/4x - 1) + (3/4x - 2)
To add the fractions with the same denominator, we add the numerators:
(3/4x + 3/4x) + (-1 - 2) = 6/4x + (-3)
Simplifying further:
6/4x - 3
Now, we can simplify the fraction by reducing it to lowest terms. Both the numerator and denominator can be divided by 2:
(6/2)(1/4x) - 3 = 3/2x - 3
Therefore, the simplified expression is:
3/2x - 3